Application of domestic greywater for irrigating agricultural products: A brief study. (February 2020) - Gorgich, M.; Mata, T.M.; Martins, A; Caetano, N.S.; Formigo, N.
Abstract: The decline in annual rainfall, coupled with the growing demand for water in agricultural fields, triggered a new crisis in today's world. Thus, the focus is on finding solutions to new water resources. Taking a look at the normal daily life, most of the households' effluents can be ranked into a less-polluted category, called greywater. Excluding human dejects, greywater comprises the outflow from washing machines, dishwashers and bathtubs. It is considered an effluent with a more economic treatment, because it contains less microbial pollution. Hence, this work revises the effects of greywater irrigation on the quality of crops, and provides a comprehensive study of the effects of greywater on the quality of soil. Furthermore, a comprehensive discussion is carried out to evaluate the energy consumption of facilities for both greywater and wastewater treatment to provide water used in irrigation. It also addresses current methodologies for treating greywater and evaluates the effects of crops irrigation with treated and untreated greywater, indicating the type of treatment chosen depending on the type of crop to be irrigated.